EFFICIENCY OF CRYOLYSIS AT SAT CATTLE DURING THE EXTRACTION OF MALIGNANT NEOPLASMS ON EYELIDS - Кулинич, С. М. (Scientific Progress & Innovations, 2014)
The symptomatology of malignant neoplasms of eyelids sat cattle is found out. Tested method of cryolysis of malignant neoplasms of eyelids at sat cattle. Efficiency of the procedures in a postoperative period in the dynamics of clinical and morphological indexes of blood is defined. It is set by planimetric researches that till 15th day reduction of wounded defect of relatively initial indexes was 58,0%. At the 20th day scars were barely noticeable and was only 11,1% according the initial data.